Towards a conceptualisation of Order Picking 4.0. (September 2021) - Winkelhaus, Sven; Grosse, Eric H.; Morana, Stefan
Highlights: Derives a theory-driven definition of Order Picking 4.0. Presents a sociotechnical order picking system framework of supportive and substitutive technologies. Provides a systematic literature review on the state-of-knowledge of Order Picking 4.0. Concludes that many concepts of Order Picking 4.0 have not yet gained attention in research. Outlines future research possibilities according to the sociotechnical order picking system framework. Abstract: Order picking is a key task in almost all supply chains and has a significant effect on operational efficiency of warehouses. Although most companies still rely on manual order picking, research on diverse possibilities to automate order picking tasks or support human order pickers with technology is increasing rapidly. This paper conceptualises Order Picking 4.0 (OP 4.0), considering substitutive and supportive technologies. Based on a conceptual background, a framework for OP 4.0 as a sociotechnical system is developed. A systematic literature review is performed to assess the state of knowledge in this field, and prospective research opportunities in OP 4.0 are highlighted.